Case study on building condition at UniMAP campus, Pauh Putra - Siti Sara Abdul Halim (School of Environmental Engineering, University Malaysia Perlis, 2012)
Structural damage is quite common phenomenon happen in construction industry. Its can occur especially on building and it very difficult to care or defect the cause of damage. Structural damage such as cracking, settlement, and leakage may lead to loss of structural integrity, gradual failure and in worst case even sudden shear failure of the structure in which could endanger line and properties of the public. This study is aim to utilize data on structural damage from questionnaire and testing and transform to statistical data. The objective of this research are to study and determine the structural damage on building due to construction work nearby, determine the level of damage for safety factor and build the statistical data, analyze the cause of structural damage. The analysis shown that, there are three type of damage structural damage on building at UniMAP campus. The types of damage are cracking, settlement and leakage. The result found that are relation between the adjacent new construction works however the primary cause of building damage is difficult to determine. Other factor contribute to the problems can also be lacking of supervision and not incompliance of the specification of materials. Prompt action and attention must be given by the authorized bodies in the construction industry to overcome the problem.